A 60 Years Old Woman with Ganglion Cyst of Popliteus Tendon Sinistra - Illahi, Faricha Kurnia; Mubarak, Abdul Hakam (Muhammadiyah Medical Journal, 2022)
The popliteal ganglion, also known as Baker's cyst, is an abnormal, fluid-filled distension of the gastrocnemius-semimembranosus bursa. These cysts rarely manifest alone and are often associated with intra-articular pathology and inflammatory conditions, such as osteoarthritis, meniscus tears, and rheumatoid arthritis. A 60-year-old woman came to the surgery clinic of Dr. Sayidiman Magetan hospital with complaints of lumps in the left knee crease. The patient noticed a lump in the crease of her left knee for two months. The patient said she did not feel pain in the lump, but the patient sometimes felt stiffness in the lump area when the patient worked in the fields. The localization status on inspection showed a mass in the popliteal area of the knee, which was round and well-defined. On palpation there is no pain, and can be moved mobile. Non-medical management is surgery/extirpation of the tumor mass.